The clinical outcomes of total femur prosthesis in patients with musculoskeletal tumors - Kakimoto, Takuya (SICOT J, 2019)
Introduction: Reconstruction using a total femur prosthesis (TFP) remains a challenging procedure in musculoskeletal tumor surgery. The purpose of this study was to show the clinical outcomes of total femur replacement (TFR) in our institute. Methods: Nine patients underwent reconstruction with a TFP after the wide resection of malignant bone and soft-tissue tumors of the femur between January 2003 and April 2014. The mean age of the patients at the time of TFR was 47.5 years, and the mean follow-up period was 52.9 months. The histological diagnoses were as follows: bone sarcoma (n = 4), soft-tissue sarcoma invading the femoral bones (n = 4), and metastatic bone tumor (n = 1). Results: The oncological outcomes were as follows: three patients achieved continuous disease free, two patients were alive with disease, and four patients died from disease. The 3- and 5-year overall survival rates were 88.9% and 55.6%, respectively. The rate of the overall survival in patients with primary bone tumors (100% at 5 years) was significantly better than that in patients with primary soft tissue sarcomas (0% at 5 years) (p = 0.015). A deep infection occurred postoperatively in one patient, but the patient was successfully treated with surgical debridement and revision surgery. There were no patients who showed dislocation or aseptic loosening. The mean Musculo-Skeletal Tumor Society functional score was 58.5% (46.7–80.0), with scores of 65.5% in patients with a primary bone tumor and 50.8% in those with a primary soft-tissue sarcoma. Discussion: In the present study, the patients who underwent TFR due to bone invasion by soft tissue sarcoma had a worse prognosis than the bone sarcoma patients.